The Use of Squid Game Simulation for Challenging Students' Vocabulary Mastery - Chonnia, Irannia Uma; Izzah, Lidiyatul (JOLLT Journal of Languages and Language Teaching, 2022)
Applying Squid game simulation is one of the effective techniques for English teachers who want to allow their students practice in the target language. This game allows students not only to practice English forms that they already acquired, but also allow them to improve new vocabularies and English structures. Therefore, this study aims to determine the improvement of students' vocabulary mastery skills in English lessons using a squid game simulation, namely Ddakji game simulation, and Green light Red Light game simulation. The game simulation is designed to enhance students’ vocabulary mastery at elementary schools. The subject of this research is a second grader at SDN Pondok Benda 01 at the academic year 2021/2022 consisting of 30 students. The method used in this study is a qualitative method with classroom practice. The results of this study indicate that there is an increase in students' vocabulary mastery skills. The achievements in the practice class are effective, students feel happy and feel challenged to want to learn more English. The squid game simulation improves the vocabulary mastery of students in second grade at SDN Pondok Benda 01.